2020
DOI: 10.1016/j.jbusres.2019.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in legal services: The practices that influence ideation and codification activities

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…It also maps out areas of opportunity for innovation uptake that have not seen enough 'investment' yet but are acknowledged by legal professionals as fields where innovative interventions could be timely and meaningful. Our study, which drew from the RBV and PBV elements to inform the nature, context, and content of data collection (focussing on human resources and organizational capital issues, the efficiency of legal processes, technology uptake, and knowledge transfer), thus highlights some of the misconceptions of innovation drawing similarities to Bourke, Roper, and Love (2020) conceptual framework around 'activities' and 'practices'.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also maps out areas of opportunity for innovation uptake that have not seen enough 'investment' yet but are acknowledged by legal professionals as fields where innovative interventions could be timely and meaningful. Our study, which drew from the RBV and PBV elements to inform the nature, context, and content of data collection (focussing on human resources and organizational capital issues, the efficiency of legal processes, technology uptake, and knowledge transfer), thus highlights some of the misconceptions of innovation drawing similarities to Bourke, Roper, and Love (2020) conceptual framework around 'activities' and 'practices'.…”
Section: Discussionmentioning
confidence: 99%
“…An important constituent of the professional service law firm is the knowledge, networks, skills, and performance that is embodied and embedded in its partners and lawyers, where purchasing idiosyncratic knowledge bases, skills, and often the experiences of legal professionals (Beaverstock 2004;Beaverstock, Taylor, and Smith 1999;Bourke, Roper, and Love 2020). Significant changes in technology, client sophistication, and general resistance to change have brought the tenuous viability and effectiveness of the traditional law firm business model in need of a paradigmatic shift (Moore and Haji 2017).…”
Section: Literature Review and Theoretical Underpinning Of The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The growing attention on human sustainability might clash with the thriving challenges of continuous innovation required by sophisticated clients; the need to pursue crescent efficiency creates increasing pressure on people (Smets, 2016). Indeed, in professional service practices, innovation capacity strongly depends on people rather than on technological infrastructures (Bourke, Roper & Love, 2020). Previous studies have also shown how managerial practices implemented to increase human sustainability had an unexpected positive impact on innovation capacity (Smets, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%